THE ROLE OF NATIONAL VALUES IN INCREASING ECOLOGICAL AWARENESS AND RESPONSIBILITY AMONG YOUTH - qizi, Kayumova Lobar Zayniddin (Research Focus International Scientific Journal, 2026)
The article presents reflections on the role of national values in raising environmental awareness and responsibility among young people. It also analyzes the regulation of ecological balance in Uzbekistan, important aspects that young people need to understand, and its impact on the development of the country.